Pengabdian di Pusat Jagaan dan Rawatan Orang Tua Al-Ikhlas di Selangor, Malaysia: Upaya Peningkatan Kesejahteraan Lansia oleh Universitas Muhammadiyah Riau - Wira Ramashar; Nur Fitriana; Cellien Patricia; Hanum Nur Rahmadhani (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2026)
This community service activity was carried out by a team from Muhammadiyah University of Riau at the Al-Ikhlas Elderly Care and Nursing Center in Selangor, Malaysia, with the aim of improving the well-being of the elderly through social, spiritual, and educational approaches. The activities were conducted in a participatory manner through senior exercise classes, art therapy, basic financial management education, and spiritual guidance. Of the 44 elderly individuals targeted by the program, 30 (68.18%) actively participated in the activities, while the remaining 14 were unable to participate due to health conditions. Results from observations and informal interviews indicated that the activities had a positive impact on the elderly, as evidenced by increased enthusiasm, social interaction, and participant engagement throughout the program. In addition to benefiting the elderly, these activities also fostered empathy, social awareness, and learning experiences among students as they interacted with a vulnerable group. It is hoped that this program will serve as a model for sustainable, cross-border community service rooted in humanitarian values.